PKW Jambu Gondangmanis Produk Unggulan Kab. Jombang Eny Dyah Yuniwati, Indah Prihartini dan Dewi Tri Wulandari - Eny Dyah Yuniwati; Indah Prihartini; Dewi Tri Wulandari (Jurnal ABM Mengabdi, 2017)
Jombang regency has superior product of Jambu gondangmanis, namely guava, planted in Gondangmanis Village, Kec. Bandar Kedungmulyo. The original name is guava Darsono (Javanese languange) and the latin (Syzygium malaccense). The cashew is currently extinct, but in Gondangmanis Village, the guava can grow well and the production of many, is a staple in the village. Guava has potential, among others, economic value is quite high In the management of this cashew production continues to decline due to decreased soil fertility and lack of maintenance. In addition, the absence of post-product products if cashew, which can be added value. This added value to raise the area of ​​Gondangmanis Village became one of the leading locations of Jambu Gondangmanis products that exist only in the village of Gondangmanis Kedungkandang district, Jombang. The goal to be achieved is to create the superiority of local guava gondang manis especially Gondangmanis Hamlet and Gondanglegi Hamlet in line with the local government program of Jombang which will feature local seeds of the region. The method used is to apply a technology that is implemented in a comprehensive, integrated and sustainable. The outcomes that have been achieved are social mapping of cashew gondangmanis farmers, training of Land Husbandry technology (especially organic fertilizer processing, pest plant eradication) and diversification training of post-cashew products into additional guava gondangmanis products (instant drinks, jams, candied sweets, and jelly ). Diversification training of superior product of jambu gondang manis and the result is very satisfactory, Jambunya farmers are very excited to make the training as a means for the development of village products.